PENDIDIKAN KEWARGANEGARAAN MENGOPTIMALISASIKAN PEMAHAMAN PERBEDAAN BUDAYA WARGA MASYARAKAT INDONESIA DALAM KAJIAN MANIFESTASI PLURALISME DI ERA GLOBALISASI - Muhammad Mona Adha (Jurnal Ilmiah Mimbar Demokrasi, 2015)
Pluralism in Indonesia is a wealth of experience to the citizens to be able to coexist in harmony. The main value of mutual respect and love between people is an important concern in Indonesia in the future to build a more cultured. Discourse of "global village" is a part of life's internalization structure that should be able to be adapted as a process of modern life in the era of globalization. Values ​​corresponding to the ideal conception of Indonesian culture can be developed that do not fade due process undertaken transnational citizens in generating diversity. Education, understanding, pluralistic, and democratic become an absolute key to contribute in teaching the people to live in harmony in unity and unity.